Intercultural research and training in the Movimento di Cooperazione Educativa - Maura Tripi (University of Bologna, 2022)
The paper presents the research and training experiences with an intercultural perspective, developed in the Movimento di Cooperazione Educativa (MCE). Firstly, the Gruppo Nazionale di Antropologia Culturale (GNAC), born in the 70s, was committed to deconstruct the ethnocentric frames in which scholastic knowledge, especially in the didactics of history, was built in the educational contexts. Secondly, the Scuola Interculturale di Formazione (SIF), which arose in the second half of the 90s, claims a specific intercultural training in light of more and more heterogeneous and complex school contexts and new professional training needs. The paper presents some evidence collected by using both bibliographic sources and oral histories, to improve and spread a reflective, democratic and cooperative perspective in multicultural educational contexts.